Not Seeing Is Believing: Ritual Practice and Architecture at Chalcolithic Çadır Höyük in Anatolia - Laurel Darcy Hackley; Burcu Yıldırım; Sharon Steadman (Religions, 2021)
Chalcolithic religious practice at the site of Çadır Höyük (central Anatolia) included the insertion of ritual deposits into the architectural fabric of the settlement, “consecrating” spaces or imbuing them with symbolic properties. These deposits are recognizable in the archaeological record by their consistent use of ritually-charged material, such as ochre, copper, human and animal bone, and certain kinds of ceramics. During the 800-year period considered in this paper, the material practice of making these ritual deposits remained remarkably consistent. However, the types of spaces where the deposits are made change as shifting social organization reforms the divisions between private and public space.